Analisis Yuridis Penanganan Perkara Perdata dengan Mediasi untuk Meneguhkan Esensi Negara Hukum di Pengadilan Negeri Tanjungpinang Kelas 1A - Ratna Susanti (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
In Article 7 paragraph (1) Perma No. 1 of 2016 it is stated that the parties and or their legal representatives are required to take mediation in good faith. The objectives of this research are; To find out the Legal Arrangements regarding the Handling of Civil Cases in Indonesia; To find out the implementation of the handling of civil cases by mediation; To find out the factors that become obstacles or obstacles as well as efforts to handle civil cases by mediation. This study uses a descriptive method with normative and sociological research types using a normative approach (legal research) to obtain primary data through field research (research). The results showed that; (1) Legal arrangements for mediation in civil cases based on Supreme Court Regulation No. 1 of 2008 are not effective in the settlement of civil cases in court from a time perspective, so it will extend the time, which in the end cannot fulfill the principles of simple, fast, and low-cost justice; (2) The implementation of mediation according to the Regulation of the Supreme Court no. 1 of 2008 is less effective because mediation is only to carry out its formal mechanism, does not seek to find the best solution in handling cases, and disputes that are submitted to the court; (3). The obstacles in taking the mediation procedure carried out by the parties in the District Court and the Supreme Court are caused by: (1) the factors of the parties; (2) No Good Faith Factor; (3) the inability of the mediator factor; (4) Factors Lack of Advocate Support through Mediation.